1992
DOI: 10.3354/meps091163
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and chromosomal aberrations during embryonic development in dab Limanda limanda

Abstract: During the Bremerhaven Workshop, ichthyoplankton samples were collected with horizontal subsurface hauls at 28 stations from the inner German Bight to the Dogger Bank. Directly after being caught fish embryos were examined a l~v e for morphological developmental defects under a dissecting microscope. Investigations on chromosomal aberrations were confined to preserved blastula stages of dab and were carried out later in the laboratory. Main species sampled were dab Limanda limanda, plaice Pleuronectes platessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 12 publications
(12 reference statements)
0
11
1
Order By: Relevance
“…These pathological methods of investigation, which were mainly limited to gross inspection, have revealed a variety of spatial and temporal trends in fish disease patterns in the North Sea (Bucke et al 1984, Bucke 1988, 1991, Bucke & Waterman 1988, Dethlefson 1988. This epidemiological type of approach can be complemented by the application of techniques which operate at the molecular, cellular and tissue level of organisation (Kohler 1989, Moore 1990, 1992a, b, Moore & Simpson 1991, Stegeman & Lech 1991, Varanasi & Stein 1991, Cameron & Berg 1992, Kohler et al 1992, Lowe et al 1992, Moore & Evans 1992. The combined methodology coupled with the use of supportive laboratory bioassays should help to define causal links between some classes of contaminant and specific types of toxic injury in fish.…”
Section: Introductionmentioning
confidence: 99%
“…These pathological methods of investigation, which were mainly limited to gross inspection, have revealed a variety of spatial and temporal trends in fish disease patterns in the North Sea (Bucke et al 1984, Bucke 1988, 1991, Bucke & Waterman 1988, Dethlefson 1988. This epidemiological type of approach can be complemented by the application of techniques which operate at the molecular, cellular and tissue level of organisation (Kohler 1989, Moore 1990, 1992a, b, Moore & Simpson 1991, Stegeman & Lech 1991, Varanasi & Stein 1991, Cameron & Berg 1992, Kohler et al 1992, Lowe et al 1992, Moore & Evans 1992. The combined methodology coupled with the use of supportive laboratory bioassays should help to define causal links between some classes of contaminant and specific types of toxic injury in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Water column tests conducted during this international study showed no evidence for widespread contamination and toxicity other than in the surface micro-layer (Hardy & Cleary 1992, Thain 1992. Dab eggs and embryos are found primarily near the surface of the water column (Cameron & Berg 1992, Rijnsdorp et al 1992. Reports by Norberg (1990) and Preston & Merrett (1991) suggest that major air-borne contaminant inputs to the North Sea occur.…”
Section: Status Of North Sea Sedimentsmentioning
confidence: 91%
“…Preneoplastic liver lesions and epidermal ulceration in dab were found, not only in nearshore fish but also, by some measures, offshore over the Dogger Bank. The frequency of abnormalities and malformations in fish embryos and larvae in the plankton was elevated in nearshore waters, then declined offshore but increased again over Dogger Bank (Bucke et al 1992, Cameron & Berg 1992, Hardy & Cleary 1992.…”
Section: Integrative Assessmentmentioning
confidence: 99%
“…radiation and chemicals). Owing to the possibility that many water pollutants may cause enhanced frequency of chromosomal aberrations in fish, cytogenetic tests are actively used in environmental genotoxicity studies (Al‐Sabti 1991; Cameron and Berg 1992; Hose and Brown 1998).…”
Section: Introductionmentioning
confidence: 99%